2010
DOI: 10.1371/journal.pone.0013979
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Co-Operation between the Epstein-Barr Virus EBNA3 Proteins in the Manipulation of Host Gene Expression and Epigenetic Chromatin Modification

Abstract: Epstein-Barr virus (EBV) is able to drive the transformation of B-cells, resulting in the generation of lymphoblastoid cell lines (LCLs) in vitro. EBV nuclear proteins EBNA3A and EBNA3C are necessary for efficient transformation, while EBNA3B is dispensable. We describe a transcriptome analysis of BL31 cells infected with a series of EBNA3-knockout EBVs, including one deleted for all three EBNA3 genes. Using Affymetrix Exon 1.0 ST microarrays analysed with the MMBGX algorithm, we have identified over 1000 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
154
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(177 citation statements)
references
References 80 publications
23
154
0
Order By: Relevance
“…3A). Previous reports have detected elevated ADAM 28 expression in EBV-negative BL cells (BL31) infected with a virus from which EBNA 3C has been deleted compared to wild-type virus-infected cells, implicating EBNA 3C as a repressor of ADAM28 (52). Our data further demonstrate that EBNA 3C can repress ADAM28 expression independently of other EBV latent proteins.…”
Section: Resultssupporting
confidence: 76%
“…3A). Previous reports have detected elevated ADAM 28 expression in EBV-negative BL cells (BL31) infected with a virus from which EBNA 3C has been deleted compared to wild-type virus-infected cells, implicating EBNA 3C as a repressor of ADAM28 (52). Our data further demonstrate that EBNA 3C can repress ADAM28 expression independently of other EBV latent proteins.…”
Section: Resultssupporting
confidence: 76%
“…We next analyzed whether, in addition to more aggressive growth, B cells transformed with EBNA3BKO in vitro and in vivo share other phenotypic characteristics. We previously observed that the expression profile of EBNA3BKO-transformed B cells differs from that of their wtBAC-transformed counterparts, and many of the differentially expressed genes encode cell surface proteins (5). We confirmed the differential expression of 6 such genes by flow cytometry.…”
Section: Ebna3bko-transformed B Cells Have a Growth Advantage In Vitrsupporting
confidence: 71%
“…We generated LCLs with bacterial artificial chromosomederived (BAC-derived) EBNA3B-deleted EBV (referred to herein as EBNA3BKO) and identified genes that differed in expression from wild-type EBV-infected LCLs (ref. 5 and see below). These genes included a number of cell surface markers, chemokines, and potential oncogenes, which prompted us to investigate the impact of EBNA3B deletion in vivo.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations